ASURANSI JIWA UNIT LINK DITINJAU DARI HUKUM ASURANSI DAN HUKUM INVESTASI (Lex Jurnalica, 2022)
Abstract Indonesia as a developing country has increased public literacy regarding the financial services industry, one of which is insurance. Currently, insurance companies continue to develop their products to become more attractive insurance products for the public with the aim of increasing public utility for insurance products. One of the most widely offered insurance products by insurance companies is the unit-linked life insurance product. This unit-linked life insurance product is intended to attract more people to insurance where in addition to providing protection features, it also provides investment features for policyholders. Unit-linked insurance continues to develop every year, which can be seen from the growth of unit-linked insurance premium income which continues to increase, namely in 2015, unit-linked insurance premium income was Rp. 57.21 trillion or an increase of 9.68% from the previous year of IDR 52.16 trillion. The increasing development of insurance companies with unit-linked life insurance products is of course the basis for the author to review this writing from a legal perspective with the aim that the public understands the basis of insurance associated with investment.Keywords : Insurance, Unit Link, InvestationAbstrak Indonesia sebagai negara berkembang telah meningkatnya literasi masyarakat mengenai industri jasa keuangan salah satunya asuransi. Saat ini perusahaan asuransi terus mengembangkan produknya agar menjadi produk asuransi yang makin menarik bagi masyarakat dengan tujuan untuk meningkatkan utilitas masyarakat terhadap produk asuransi. Salah satu produk asuransi yang saat ini paling banyak ditawarkan oleh perusahaan asuransi adalah produk asuransi jiwa unit link. Produk asuransi jiwa unit link ini dimaksudkan untuk makin menarik masyarakat dalam berasuransi dimana di dalam produk tersebut selain memberikan fitur proteksi juga menyediakan fitur investasi bagi pemegang polis. Asuransi unit link terus mengalami perkembangan setiap tahunnya, yang dapat dilihat dari pertumbuhan pendapatan premi asuransi unit link yang terus meningkat yaitu pada tahun 2015, pendapatan premi asuransi unit link sebesar Rp57,21 triliun atau mengalami peningkatan sebesar 9,68% dari tahun sebelumnya yaitu sebesar Rp52,16 triliun. Meningkatnya perkembangan perusahaan asuransi dengan produk asuransi jiwa unit link tentunya menjadi landasan penulis meninjau penulisan ini dari segi hukum dengan tujuan agar masyarakat memahami dasar adanya asuransi yang dikaitkan dengan investasi.Kata kunci : Asuransi, Unit Link, Investasi